The Effect of the Acting Play Script Technique in Enhancing Speaking Skill for the Students of Senior High School - Rini Novia Candra Dewi; Shierly Novalita Yappi (International Journal of English and Applied Linguistics (IJEAL), 2023)
This research discusses the effect of the acting play script technique in enhancing the speaking skills of students in senior high school. The research used an experimental design called a quasi-experiment and the scoring used a T-test. There were two types of groups involved in this study to compare the results of the speaking skills after the Acting Play Script. One class as the control group only got the pre-test and post-test while the other class as the experiment group got the pre-test, and post-test as well, and an additional treatment called the Acting Play Script technique where the students did a speaking activity using a script made by themselves. In the control group, the speaking pre-test result showed that the mean of students in a number of 29,55 while the experimental group in a number of 30,07. After the researcher did the treatment of the Acting Play Script in the experimental group, the mean of the speaking post-test in the experimental group went up in a number of 45,5 while the mean in the control group was in a number of 40,5. Based on the result, it was concluded that the acting play script technique has an effect in enhancing student speaking skills reinforced by the rise of the students speaking test mean value in the experimental group.